Integrated Lecture Tools to Improve Student Competencies to Develop Physical Learning Media Design - I Made Astra; Upik Rahma Fitri (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
Abstract Have been developed a lecture tool for Physics Learning Media Development course. Development applies the ASSURE model, with activities: analysis stages, formulating objectives, selecting media, selecting course materials, developing lecturing tools, implementations to collect student responses, and evaluations. The tools consist of syllabus, hand out, Student Activity Sheet, and Student Performance Appraisal Sheet. This research product has been tested on Physics Education Student of FMIPA UNJ. Student's response to lectures was collected using a fourteen-item questionnaire. The average score given by the students to the lecture is 72.03 good category. Student Performance Making Learning Media Design using this research product average 77,95 good category. Based on the student's response and the student's performance score in making the design of physics learning media, it can be concluded that the integrated lecture tools developed are worthy to be used as teaching materials for the Context Based Learning Media Learning course. Keywords: Lecture tools, Media design, Media development. Abstrak Telah dikembangkan perangkat perkuliahan untuk mata kuliah Pengembangan Media Pembelajaran Fisika. Pengembangan menerapkan penelitian pengembangan yang mengacu pada model ASSURE, dengan tahapan analisis kebutuhan, merumuskan tujuan, memilih media, memilih materi perkuliahan, menyusun perangkat perkuliahan, implementasi untuk mengumpulkan respon mahasiswa, dan evaluasi. Perangkat perkuliahan yang dikembangkan terdiri dari silabus, hand out, Lembar Kegiatan Mahasiswa, dan Lembar Penilaian Kinerja Mahasiswa. Produk penelitian ini sudah diujicobakan terhadap mahasiswa Pendidikan Fisika FMIPA UNJ. Respon mahasiswa terhadap perangkat perkuliahan dijaring menggunakan angket yang terdiri dari empat belas butir. Rerata skor yang diberikan mahasiswa terhadap perangkat perkuliahan adalah 72,03 kategori baik. Kinerja mahasiswa Membuat Desain Media Pembelajaran menggunakan produk penelitian ini rerata 77,95 kategori baik. Berdasarkan respon mahasiswa dan nilai kinerja mahasiswa dalam membuat desain media pembelajaran fisika, dapat disimpulkan bahwa perangkat perkuliahan terintegrasi yang dikembangkan layak digunakan sebagai bahan ajar untuk mata kuliah Pengembangan Media Pembelajaran Fisika Berbasis Konteks. Kata kunci: Perangkat perkuliahan, Desain media, Pengembangan media.